High-precision deformation mapping in finFET transistors with two nanometre spatial resolution by precession electron diffraction - Cooper, David (Appl Phys Lett, 2017)
Precession electron diffraction has been used to systematically measure the deformation in Si/SiGe blanket films and patterned finFET test structures grown on silicon-on-insulator type wafers. Deformation maps have been obtained with a spatial resolution of 2.0 nm and a precision of ±0.025%. The measured deformation by precession diffraction for the blanket films has been validated by comparison to energy dispersive x-ray spectrometry, X-Ray diffraction, and finite element simulations. We show that although the blanket films remain biaxially strained, the patterned fin structures are fully relaxed in the crystallographic planes that have been investigated. We demonstrate that precession diffraction is a viable deformation mapping technique that can be used to provide useful studies of state-of-the-art electronic devices.